Introduce and Increase Sunday School Children's Interest In Learning Basic English And Training In Guitar and Piano Instruments at HKBP GKJ Sehati Kampung Kolam - Siahaan, Restu Berka; Marbun, Yehezkiel; Panggabean, Ance Juliet (Journal of Community Research and Service, 2023)
Thematic Field Practice (PLT) is a compulsory subject at the Faculty of Languages and Arts and is a direct teaching and learning process that puts into practice the knowledge learned in lectures. Students must acquire knowledge and skills and apply them in their community, whether in the school community, industrial community, institutional community or general community, depending on their field of study. In implementation of thematic field practice activities requires responsibility, discipline, thoroughness or accuracy and high patience in follow social norms in society, as well as in steps learning in teaching activities, training and mentoring children elementary school. This teaching practice provides a direct description of how the learning process works, how to interact with Sunday school children, how to convey material well and with understanding, as well as how to understand their very different characteristics. With this English class and this music art class, Sunday school children not only learn Indonesian but also learn foreign languages and learn music with their enthusiasm the first time they learn English and music, it is hoped that students will be able to hone and continue learning , English language training and music art training in order to improve human resources which will always increase with the times.